Understanding the Trending of Laboratory Investigations as Part of Quality Management Systems-A Quality Assurance Perspective - Naduparambil Reji, Anupriya; Koland, Marina; Divate Satyanarayana, Sandeep (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: In the pharmaceutical sector, the effectiveness of the laboratory and its compliance with regulatory standards is critical in establishing an effective Quality Management System (QMS). Objectives: The present study was undertaken to carry out the laboratory investigation which is an integral aspect of a QMS, and is often used to investigate non-conformity in results in order to determine the most possible root cause. Materials and Methods: Laboratory investigation data is retrieved from a successful company involved in pharmaceutical product R&D which was used to identify the critical root causes by using 5 M method of root cause analysis. CAPA strategies were implemented based on trending results to prevent their recurrence. Results: From the root cause analysis it was found that manpower was found to be the potential root cause (47%) among the 5Ms. Sinceall these events resulted from human error, identification of the analysts responsible for these errors was important for finding out effective CAPA. The trending of the analysts involved in the potential error assisted in identifying the person who committed the same type of event several times. Conclusion: HPLC and GC are well-known instruments that are sensitive to a number of problems. As a result, analysts must exercise extreme caution while employing these instruments. In comparison to manpower and machine, method, material, and measurement errors are shown to be less frequent.
Keywords: Laboratory investigations; Quality management system; CAPA; HPLC; GC